Burundi : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses the Poverty Reduction Strategy Paper (PRSP) for Burundi. The PRSP comes two and a half years after the approval in January 2004 by the Executive Boards of the IMF and the World Bank of the Interim PRSP (I-PRSP). The PRSP is also the outgrowth of a long period of negotiations encouraged and supported by the international community. The PRSP presents a medium- and long-term development vision for Burundi and sets out bold poverty reduction objectives, which are consistent with the government's 2005-10 priority program and the Millennium Development Goals.